2016
DOI: 10.1002/ajmg.a.37931
|View full text |Cite
|
Sign up to set email alerts
|

An unusual presentation of Kabuki syndrome with orbital cysts, microphthalmia, and cholestasis with bile duct paucity

Abstract: Kabuki syndrome (KS) is a rare developmental disorder characterized by multiple congenital malformations, postnatal growth retardation, intellectual disability, and recognizable facial features. It is mainly caused by mutations in either KMT2D or KDM6A. We describe a 14-year-old boy with KS presenting with an unusual combination of bilateral microphthalmia with orbital cystic venous lymphatic malformation and neonatal cholestasis with bile duct paucity, in addition to the typical clinical features of KS. We id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…In particular, a mutation in KMT2D at 12q13.12 accounts for 55–80% of KS cases, whereas 9–14% of KMT2D -negative patients have a deletion or mutation in KDM6A at Xp11.3 [23]. Bögershausen et al reported on a KS patient with a KMT2D mutation who presented with neonatal cholestasis with bile duct paucity in addition to the typical clinical features of KS, although their case did not show pathogenic variants in either JAG1 or NOTCH2 ; they hypothesized that the KMT2D mutation might have affected several key Notch signaling components [24]. KDM6A encodes lysine-specific demethylase 6A (UTX), a JmjC domain-containing protein that specifically demethylates the H3K27me3/me2 mark [25].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, a mutation in KMT2D at 12q13.12 accounts for 55–80% of KS cases, whereas 9–14% of KMT2D -negative patients have a deletion or mutation in KDM6A at Xp11.3 [23]. Bögershausen et al reported on a KS patient with a KMT2D mutation who presented with neonatal cholestasis with bile duct paucity in addition to the typical clinical features of KS, although their case did not show pathogenic variants in either JAG1 or NOTCH2 ; they hypothesized that the KMT2D mutation might have affected several key Notch signaling components [24]. KDM6A encodes lysine-specific demethylase 6A (UTX), a JmjC domain-containing protein that specifically demethylates the H3K27me3/me2 mark [25].…”
Section: Discussionmentioning
confidence: 99%
“…KS1 is characterized by several clinical manifestations including cardinal facial gestalts (long palpebral fissures, eversion of the lower lateral eyelids, arched eyebrows, depressed nasal tip, palate malformations, and large prominent ears), feeding difficulties, digital and hand anomalies, cardiovascular defects, skeletal and growth abnormalities, immune system dysregulation, anxiety and sleep difficulties, neonatal hypotonia, renal anomalies, and endocrine abnormalities (Adam et al, 2019; De Leon & Stanley, 2017; Niikawa et al, 1981; Rapp et al, 2022; Stagi et al, 2016; Yap et al, 2019). Other possible manifestations include orbital vascular malformations and cholestasis, cleft hand, epilepsy, microphthalmia, and pilomatricoma, among many others (Bernier et al, 2017; Bögershausen et al, 2016; Bruni et al, 2021; Huh et al, 2011; Kamada et al, 2019; McVeigh et al, 2015).…”
Section: Ks1 In the Clinicmentioning
confidence: 99%
“…All monogenic causes were previously associated with MAC except EPHA2, for which association with microphthalmia was validated and published, 19 3, figure 2B). [19][20][21][22][23][24][25][26][27] According to Association for Clinical Genomic Science classification guidelines, ALDH1A3 variant c.104T>C;p.(Phe35Ser) in patient 22-1 is a variant of 'uncertain significance'. However, the multidisciplinary team considered this patient's phenotype to be compatible with reported ALDH1A3 cases and there were no other relevant mutations found in MAC panels applied to this patient's genome data.…”
Section: Molecular Diagnosismentioning
confidence: 99%